Advances in Catalytic Isomerization Using Heteropolyacid-Based Nanocomposites: A Comprehensive Review - Awadh, Alaa J.; Ammar, Saad H. (Al-Nahrain Journal for Engineering Sciences, 2024)
Catalytic isomerization is a process used to increase the octane number of light naphtha fraction and thus aids in extending the life of automobile engines. Researchers are still working to prepare more effective and less expensive isomerization catalysts to replace the costly previous catalysts. Ongoing challenges in this field seek to design highly active isomerization catalysts operated under moderate conditions while keeping high branched-isomer selectivity. Heteropolyacids (HPA) have been presented as the most capable substitutes to fulfill the requirements. They are considered bifunctional catalysts that perform dehydrogenation /isomerization followed by hydrogenation because of their firm acidity and redox properties. Some catalytic-isomerization studies were started utilizing HPA in combination with platinum, which significantly improves the selectivity and stability. Thus, HPA-based bifunctional catalysts can provide enough acid and hydrogenation–dehydrogenation sites sufficiently. However, the most ongoing challenge in this field is the poor thermal stability of HPAs, which limits their use at higher temperatures for vapour-phase reactions. This review aims to highlight the recent progress in catalytic isomerization of alkanes using heteropolyacids supported on different carriers, with and without noble metals.